Pengaruh Pemberian Berbagai Pupuk Organik pada Media Tanam Pasir Terhadap Pertumbuhan Tanaman Pakcoy (Brassica Rapa) - Amin Mbusango; Elfira Pratiwi (Lembaga Pengembangan Kinerja Dosen, 2023)
Organic fertilizers are materials derived from plant residues, and animal waste, both those that have undergone decomposition and those that are undergoing a decomposition process that functions to add nutrients. Substantially organic fertilizers are composed of humus and non-humus materials so that they can improve marginal soils and sand-dominated soils. The purpose of this study was to determine the effect of various organic fertilizers on sand planting media, and to determine the growth response of pakcoy on various types of organic fertilizers. The research was conducted at the Field Laboratory I Experimental Garden and Agrotechnology Laboratory of the Faculty of Agriculture, Halu Oleo University, the research took place from September to November 2020. This study was arranged in a randomized group design (RAK) with the treatment of various organic fertilizers, which were divided into; no organic fertilizer/control (B0), cow manure (B1), chicken manure (B2), comba-sheep green manure (B3), calopogonium green manure (B4). Each treatment was repeated four times as a group, resulting in 20 experimental units. Each experimental unit consisted of six polybags, resulting in a total of 120 polybags of pakcoy plants. The variables observed were plant height, number of leaves, fresh weight and dry weight of pakcoy plants. The results showed that organic fertilizer had a very significant effect on all observed growth variables of pakcoy plants. Cow manure treatment in the first and second week plant height variables showed the highest value (5.04 cm, and 6.71 cm). But in general, in the third to fifth week, the average chicken manure gave the highest growth response on the variable of plant height, number of leaves, fresh weight and dry weight of pakcoy plants.